Inhibitory activity of cold atmospheric plasma on candida albicans - Phenphichar Wanachantararak (2019)
© 2019, Walailak University. All rights reserved. Cold Atmospheric Plasma (CAP) application of dental treatment technologies has recently gained much interest. However, information regarding safety, applications, and how they work is limited. In this study, we examined the inhibitory activity of CAP against Candida albican. The Ar gas has been discharged by CAP of 100 KHz and has been produced inside 4 L/min. The system was operated with the HVRF power input 20 W and treatments of 0, 5, 10, 15 min for samples. The Candida albican standard strain used in this experiment was ATCC 10231. In order to assess the inhibitory activity of CAP against Candida albican, we employed 2 methods; the colony number count and MTT colorimetric assay. The colonies of Candida albican standard strain ATCC 10231 were significantly at 5, 10 and 15 min exposure of CAP (p < 0.05) as compared to un-treatment. According to the result of MTT colorimetric assay, we found that cell viability was significant after 10 min exposure as compared to un-treatment (p < 0.05). In summary, the overall results stated that CAP possesses the inhibitory activity against Candida albican standard strain ATCC 10231 at 100 KHz, 20 W after 5 min.